The price of advice - Péter Eső; Balázs Szentes (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
We develop a model of consulting (advising) where the role of the consultant is that she can reveal signals to her client which refine the client's original private estimate of the profitability of a project. Importantly, only the client can observe or evaluate these signals, the consultant cannot. We characterize the optimal contract between the consultant and her client. It is a menu consisting of pairs of transfers specifying payments between the two parties (from the client to the consultant or vice versa) in case the project is undertaken by the client and in case it is not. The main result of the paper is that in the optimal mechanism, the consultant obtains the same profit as if she could evaluate the impact of the signals (whose release she controls) on the client's profit estimate.
Keywords: C72; D49; D82; D83; 330; Mechanism design; information disclosure; consulting; advising; Sachverständige; Signalling; Asymmetrische Information; Theorie